Head Dressed as Night: the Imaginary of Evil and Decapitation in Fiesta en la madriguera [Down the Rabbit Hole] by Juan Pablo Villalobos - Vanegas, Orfa Kelita (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This study is centered on the symbolism of decapitation in Fiesta en la madriguera [Down the Rabbit Hole] by Juan Pablo Villalobos. This work of fiction proposes a language to refer to the decapitation of the human body as a radical expression of evil will. And even though the figuration of extreme violence is a repetitive topic in contemporary Mexican literature; what captures the reader ́s attention here is the novelty of the narrative focus, which reconstructs a narco-imaginary of evil from a child ́s perspective. As operational image of evil, the representation of decapitation makes us reflect about the inteligible nature of the human being, and constitutes a space of replies againt the politics of abjection located in the heart of the subject, society, and State.